Post-COVID Gut Dysbiosis and Its Role in Persistent Skin Disorders: A Gut–Skin Axis Perspective - Dorra Guermazi; Elias Guermazi (COVID)
The COVID-19 pandemic has led to persistent complications beyond the respiratory system, with emerging evidence highlighting the role of gut dysbiosis in long COVID. Given the established gut–skin axis, alterations in gut microbiota post-COVID-19 may contribute to persistent dermatologic conditions such as eczema, acne, and rosacea. This review explores the mechanisms by which SARS-CoV-2 disrupts the gut microbiome, leading to systemic inflammation and skin disease. Furthermore, it examines potential interventions, including probiotics, prebiotics, and dietary modifications, as microbiome-targeted therapeutic strategies for post-COVID dermatologic recovery. Understanding this link may open new avenues for treating chronic inflammatory skin conditions in long COVID patients.